Antioxidant defence and inflammatory response in professional road cyclists during a 4-day competition - Serrano, E.; Venegas, C.; Escames, G.; Sanchez-Munoz, C.; Zabala, M.; Puertas, A.; de Haro, T.; Gutierrez, A.; Castillo, M.; Acuna-Castroviejo, D. (Journal of Sports Sciences, 2010)
Cycling competitions represent an important physical overload even for well-trained individuals. In six professional cyclists, we studied the adaptive oxidative and anti-inflammatory response to a 4-day road cycling competition and its relationship with melatonin, an antioxidant and anti-inflammatory stress hormone. Blood and urine samples were collected before and after the competition. Plasma lipid peroxidation, cytokines (interleukin-1ß, interleukin-6, and tumour necrosis factor-), creatine kinase and other metabolic markers, melatonin, erythrocyte glutathione, and glutathione peroxidase and reductase activities were measured. Urinary excretion of 6-sulphatoxymelatonin was analysed. Lipid peroxidation increased after the competition, but the erythrocyte glutathione pool remained unchanged. Changes in both glutathione peroxidase and reductase activities probably account for the recycling of glutathione after exercise. Interleukin-6 (216%) and tumour necrosis factor- (159%) but not interleukin-1ß increased after exercise. A parallel increase in plasma melatonin concentrations was detected, whereas metabolic markers, including creatine kinase, showed minor modifications. Thus, professional cyclists display an adaptative response to the physical overloads in the competitions for which they are trained. Consequently, they seem to be able to regulate efficiently the intracellular oxidative stress, and prevent an exaggerated pro-inflammatory cytokines induction. A modulator role of melatonin in these adaptive responses is also supported.